2012
DOI: 10.5923/j.re.20120204.06
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and Gas Flaring Activities: a Case Study of Ebedei Area of Ukwuani LGA, Delta State, Nigeria

Abstract: The impact of gas flaring on the sustainable development was examined. The presence crude oil and natural gas is expected to serve as socio-economic driver of accelerated sustainable development of an area but the situation of oil producing areas of Nigeria is a far cry from the expected. Data was collected from eight (8) experimental sites around the gas flaring station including Obiaruku (control site), which has no gas-flaring station. Temperature and concentrations of air quality indices were determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…What is worrisome about this finding is that at this age people are still subjected to the use of rain water and river water for domestic use. Yet [17], [20] reported that the area is experiencing acid precipitation due in part to the flaring activities taking place at the adjacent community (Ebedei) and [16] reported that due to socio economic activities taking place along the Ethiope river course the river is polluted. It therefore implies that some of Owah-Abbi dwellers are forced to ingest unsafe water either for financial reasons or distance.…”
Section: Data Presentation and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is worrisome about this finding is that at this age people are still subjected to the use of rain water and river water for domestic use. Yet [17], [20] reported that the area is experiencing acid precipitation due in part to the flaring activities taking place at the adjacent community (Ebedei) and [16] reported that due to socio economic activities taking place along the Ethiope river course the river is polluted. It therefore implies that some of Owah-Abbi dwellers are forced to ingest unsafe water either for financial reasons or distance.…”
Section: Data Presentation and Discussion Of Resultsmentioning
confidence: 99%
“…Even the few privately owned borehole owners complain of not having power (for two years now) to pump water and rather resort to the use of generators. All these have either forced the people in the area to use the water from the river Ethiopie, which is polluted [16], or harvest rainwater which is acidic [17], or use less than the required amount of water per day in a household. All these problems stated have social and health implications on the people there.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study on oil palm processing plants by ) and revealed that concentration decreases as the distance from the source of emission increases. According to Ojeh (2012), as one gets farther away from a gas flaring station, the concentration of harmful gases decreases. At a gas flare site, the most hazardous area of a gas flaring location is typically located 50 to 350 meters away from the flare station (Ojeh, 2012).…”
Section: Effect Of Season and Factors That Promote The Dispersal Of P...mentioning
confidence: 99%
“…There are many oil wells in Niger delta and the flaring activities done in the environs are not sustainable as it's extremely closer to inhabited houses in the localities. (Ojeh, 2012) in his case study research on Ebedei in Delta State found that gas flaring generate extreme heat which affect the environment thereby affecting the community and threaten the achievement of sustainable development goal.…”
Section: Environmental and Health Effect Of Gas Flaring In Nigeriamentioning
confidence: 99%
“…Gas flaring has various social economic impacts on the environment and living things. (Ojeh, 2012) observes that the Niger delta has experienced sufferings and neglect from politicians, oil companies, and government officials. These sets of people enjoy the resources generated in that region but leaving scar in the heart of the people living there.…”
Section: Social and Economic Implication Of Gas Flaring In Niger Deltamentioning
confidence: 99%